2022
DOI: 10.1039/d2ra03249j
|View full text |Cite
|
Sign up to set email alerts
|

Plasticized and salt-doped single-ion conducting polymer electrolytes for lithium batteries

Abstract: Semi-solid solvent-free electrolytes are created from a single-ion conducting polymer electrolyte, a classic polymer and a plasticizing Li-salt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…Figure 8 shows plots of the dc conductivity as a function of the inverse of temperature for different MWCNT concentrations in the (PEO) 4 CF 3 COOLi electrolyte. For all systems, it is observed that the dc conductivity increases with increasing temperature following the Vogel Tamman Fulcher (VTF) equation [ 18 , 32 ]: where σ dc is the conductivity obtained in the plateau, σ 0 is the pre-exponential factor, E A is a parameter known as pseudo-activation energy, k B is the Boltzman constant, T is the absolute temperature, and T 0 stands for the temperature (below the glass transition temperature) at which the free volume, responsible for ionic conduction, disappears, and the ionic conductivity cancels out. Table 6 shows the parameters for the fitting to Equation (2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 8 shows plots of the dc conductivity as a function of the inverse of temperature for different MWCNT concentrations in the (PEO) 4 CF 3 COOLi electrolyte. For all systems, it is observed that the dc conductivity increases with increasing temperature following the Vogel Tamman Fulcher (VTF) equation [ 18 , 32 ]: where σ dc is the conductivity obtained in the plateau, σ 0 is the pre-exponential factor, E A is a parameter known as pseudo-activation energy, k B is the Boltzman constant, T is the absolute temperature, and T 0 stands for the temperature (below the glass transition temperature) at which the free volume, responsible for ionic conduction, disappears, and the ionic conductivity cancels out. Table 6 shows the parameters for the fitting to Equation (2).…”
Section: Resultsmentioning
confidence: 99%
“…Thermal analyses were performed by differential scanning calorimetry measurements, with a Setaram DSC evo 131 calorimeter, in a temperature range from 176 K to 430 K, at 10 K/min (heating rate used in many studies of polymeric systems [ 17 , 18 ]); above this temperature, no further transitions are observed. Aluminum sample holders of 30 μL and high-purity nitrogen purge gas were used.…”
Section: Methodsmentioning
confidence: 99%